(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background: Urethroplasty is the treatment of choice for long segment anterior urethral stricture. Various types of graft can be used as substitution, but now a day Buccal Mucosal Graft (BMG) is more popular with very promising results. This study was conducted to compare the outcome between dorsolateral free BMG graft and traditional staged reconstruction technique. Materials and methods: This was a hospital based quasi experimental study done prospectively on 64 patients, dividing in two groups, dorsolateral onlay BMG Urethroplasty (Group A) and Johanson’s staged Urethroplasty (Group B) from January 2016 to June 2018 for long segment (3080mm) anterior urethral stricture with a minimum 06 months follow-up. Two patients were failed to attened at follow up clinic were excluded from the study. Data were analyzed by student’s t test, and chi-square test where appropriate. Results: Total 62 patients were included in results (2 lost in follow-up) 32 patients with BMG (Group A) and 30 patients with Johanson’s urethroplasy (Group B) in 6 months follow-up where success rate of group A was 90.7% and group B 63.3% which is statistically significant. At the end of six months 22 patients (68.8%) in Group A had peak urnary flow rate more than 15 ml/sec, whereas only nine patients (33.3%) had had such flow rate in B group. Post operative complications were significantly higher in Group B. Eight patients (26.7%) in Group B had developed fistula and eleven patients (36.7%) had recurrence in Group B which is significantly higher then Group A. Conclusions: Dorsolateral onlay BMG urethroplasty is comparatively an effective technique with excellent functional outcome for long segment an- terior urethral stricture and feasible with good short term success. JCMCTA 2020 ; 31 (1) : 31-37